A consideration of what is meant by automaticity and better ways to measure it - Keatley, David; Chan, Derwin K.C.; Caudwell, Kim; Chatzisarantis, Nikos; Hagger, Martin (Frontiers Research Foundation, 2015)
A commentary on 'Predicting automaticity in exercise behaviour: the role of perceived behavioural control, affect, intention, action planning, and behaviour' by de Bruijn, G.-J., Gardner, B., van Osch, L., and Sniehotta, F. (2014). Int. J. Behav. Med. 21, 767–774. doi: 10.1007/s12529-013-9348-4